Evaluation of psychological changes using facial emotion analysis in postoperative rehabilitation treatment for patients with upper gastrointestinal cancer: A prospective study - Naoto Seriu; Shogo Sasaki; Yukako Ishida; Yasuyo Kobayashi; Tetsuro Kitamura; Yuya Mawarikado; Yosuke Uchihashi; Yusuke Inagaki; Masayuki Sho; Akira Kido (PLoS ONE, 2026)
Rehabilitation after radical gastrectomy or esophagectomy for upper gastrointestinal cancer can improve physical function and quality of life; however, objective day-to-day measures of psychological change are lacking. We aimed to test whether facial emotion analysis can quantitatively evaluate patients’ emotional responses before and after each rehabilitation session and whether these changes relate to conventional subjective/physiological stress markers and discharge physical outcomes. We conducted a single-center prospective observational study of 32 patients who underwent radical gastrectomy or esophagectomy between August 2024 and February 2025. Immediately before and after each rehabilitation session, 30 s iPad video interviews (median, six per patient) were recorded and analyzed using MAL Face Emotion software to obtain normalized scores (0%–100%) for Neutral, Happy, Sad, Angry, and Surprised emotions. Subjective stress (0–100 mm visual analog scale) and salivary α-amylase activity were collected concurrently; discharge physical function was assessed using the 6 min walk distance and Five Times Sit-to-Stand tests. Pre- and post-session values were compared using Wilcoxon signed-rank tests, and associations were examined with age-adjusted regression and Spearman correlation. Thirty-one patients completed the study without adverse events. After rehabilitation, the Happy score increased (median +3.5%, p = 0.013) and stress decreased (−1.5 mm, p = 0.025), whereas salivary α-amylase and other emotions were unchanged. Changes in the Happy score (p = 0.21) and stress (p = 0.19) did not predict discharge physical function, whereas changes in the Sad score correlated moderately with changes in salivary α-amylase (ρ = 0.45). The findings of this single-center study provide preliminary evidence supporting the feasibility of facial emotion analysis as a non-invasive, quantitative tool for real-time psychological monitoring during postoperative rehabilitation. Furthermore, our results demonstrate its potential to support a more personalized delivery of cancer rehabilitation.